The use of stimulus-stimulus pairing procedure in inducing vocal speech with nonverbal child with autism spectrum disorders - Anja GajiÄ‡; Bojana ArsiÄ‡; Sara VidojkoviÄ‡; Dragana MaÄ‡eÅ¡iÄ‡-PetroviÄ‡; Aleksandra BaÅ¡iÄ‡ (Universitas Majalengka, 2022)
Stimulus-stimulus (ss) pairing procedure can be used in a variety of ways in treatment of people with autism spectrum disorders (ASD), however it is mostly used in inducing vocal speech in nonverbal children. Research shows that using this procedure is more efficient for increasing the number of emitted words when compared to other procedures. Therefore, the aim of this case study is to examine the effectiveness of the use of ss pairing procedure in order to induce vocal speech with a nonverbal child diagnosed with ASD. At the very first session of the procedure implementation, the child spoke clear words, while in the last session, the number of spoken words per session was 192. Having in mind the effectiveness of the implemented procedure, as well as data that parents of children with ASD can be successfully trained to use this procedure in their home environment, it is important to train them to implement it correctly. This is of great importance because the majority of the children with ASD are nonverbal, and lack of communication correlates with problem behavior.